The Case for the World Health Organization’s Commission on the Social Determinants of Health to Address Sexual Orientation - Logie, Carmen (American Public Health Association, 2012)
The World Health Organization's (WHO's) social determinants of health discussion underscores the need for health equity and social justice. Yet sexual orientation was not addressed within the WHO Commission on the Social Determinants of Health final report Closing the Gap in a Generation. This omission of sexual orientation as a social determinant of health stands in stark contrast with a body of evidence that demonstrates that sexual minorities are disproportionately affected by health problems associated with stigma and discrimination, such as mental health disorders. I propose strategies to integrate sexual orientation into the WHO’s social determinants of health dialogue. Recognizing sexual orientation as a social determinant of health is an important first step toward health equity for sexual minorities.